2014
DOI: 10.1111/geb.12144
|View full text |Cite
|
Sign up to set email alerts
|

Performance of species richness estimators across assemblage types and survey parameters

Abstract: Aim A raw count of the species encountered across surveys usually underestimates species richness. Statistical estimators are often less biased. Nonparametric estimators of species richness are widely considered the least biased, but no particular estimator has consistently performed best. This is partly a function of estimators responding differently to assemblage-level factors and survey design parameters. Our objective was to evaluate the performance of raw counts and nonparametric estimators of species ric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 44 publications
0
41
0
Order By: Relevance
“…). Because the performance of species richness estimators often increases for less diverse communities (Reese, Wilson & Flather ), we expect our results to represent an optimistic or best‐case scenario that is broadly applicable to many assemblages. The example data set consisted of catch data of fish in 52 Florida lakes between 2006 and 2010 (Bonvechio et al .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…). Because the performance of species richness estimators often increases for less diverse communities (Reese, Wilson & Flather ), we expect our results to represent an optimistic or best‐case scenario that is broadly applicable to many assemblages. The example data set consisted of catch data of fish in 52 Florida lakes between 2006 and 2010 (Bonvechio et al .…”
Section: Methodsmentioning
confidence: 99%
“…However, many studies have demonstrated that the efficacy of this extrapolation depends on the number of species observed, the shape of the species‐abundance distribution (O'Hara ; Doi & Mori ) and the relative vulnerabilities of species to the sampling method (Brose, Martinez & Williams ; Walther & Moore ; Hortal, Borges & Gaspar ; Beck & Schwanghart ; Reichert et al . ; Reese, Wilson & Flather ). These inconsistencies have resulted in the development of a large number of estimators with unique properties and a plethora of scientific studies seeking the best estimator for particular systems.…”
Section: Introductionmentioning
confidence: 99%
“…The other estimators provided plausible values ranging from an average of 99 (bootstrap) to 265 (Chao) predicted species per spatial unit for an average of 79 observed species per spatial unit. The performance of asymptotic species richness estimators depends on a variety of assemblage attributes (e.g., species abundance distribution, spatial aggregation and species detection probability), sampling design and effort (Reese et al, 2014). Sources of the georeferenced occurrences are heterogeneous, although each were based on bottom trawling, in the sense that they included a diverse array of surveys and cruises with different field designs and spatial and temporal coverage (García and Armenteras, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…Some authors have demonstrated that a raw count of the number of species in an area is far from the best estimate of true species richness (Reese et al, 2014). Despite its wide appeal and apparent simplicity, accurate estimates of species richness can be remarkably difficult to achieve using only the observed number of species.…”
Section: Alpha Diversitymentioning
confidence: 99%